Promotion of next generation urologists-Construct urology of the future - Siech, C.; Bellut, Laura; Konopka, M.; Neutzer, M. (Die Urologie, 2022)
In view of the growing demand for urological care and the simultaneous demographic change, the need for urologists in Germany is increasing. Therefore, young professionals are urgently needed to ensure urological care in the future. This objective can be achieved by fascinating medical students for urology and by implementing satisfactory residency programs in clinical departments and outpatient offices. Perspectives and possible career paths should be shown to junior colleagues at an early stage. Structured research funding is needed to reconcile academic with clinical work. The German Society for Residents in Urology (GeSRU) offers young urologists a platform for networking, for representation of interests as well as for education and training.
CRIS-Team WoS Importer:2022-08-05